Decision making process for amputation in case of therapy resistant complex regional pain syndrome type-I in a Dutch specialist centre. (December 2018) - Schrier, E.; Dijkstra, P.U.; Zeebregts, C.J.; Wolff, A.P.; Geertzen, J.H.B.
Abstract: Deciding for an amputation in case of complex regional pain syndrome type I (CRPS-I) is controversial. Evidence for favorable or adverse effects of an amputation is weak. We therefore follow a careful and well-structured decision making process. After referral of the patient with the request to amputate the affected limb, it is checked if the diagnosis CRPS-I is correct, duration of complaints is more than 1 year, all treatments described in the Dutch guidelines have been tried and if consequences of an amputation have been well considered by the patient. Thereafter the patient is assessed by a multidisciplinary team (psychologist, physical therapist, anesthesiologist-pain specialist, physiatrist and vascular surgeon). During a multidisciplinary meeting professionals summarize their assessment. Pros and cons of an amputation are discussed, taking into account level of amputation and expectations about post amputation functioning of patient and team. Based on assessments and discussion a consensus based decision is formulated and the patient is informed. If it is decided that an amputation is to be performed, the amputation will follow shortly. If it is decided not to amputate, the decision is extensively explained to the patient. Incidence of patients suffering from therapy resistant CRPS-I referred for amputation is low and because referred patients are strongly in favor of an amputation, a randomized controlled trial will be difficult to perform. Hence level of evidence in favor or against an amputation will remain low. We therefore report our decision making process to facilitate discussion about this difficult and delicate matter.